(untitled) (Research, Society and Development, 2025)
The use of medicinal plants with therapeutic properties is an ancient practice and continues to be essential in the creation of natural medicines and treatments. According to the World Health Organization (WHO), a large portion of the population in developing countries uses plants for basic health care. Lavender essential oil (Lavandula angustifolia) has several therapeutic properties that make it widely used in pharmaceuticals and aromatherapy. Studies demonstrate that its compounds, such as α-pinene, terpin-4-ol and linalool, have antimicrobial, anti-inflammatory, anxiolytic and antispasmodic effects. In-depth research into these effects is crucial to expanding their safe and effective use in a variety of treatments. This study will be conducted at the Biotechnology Experimental Studies Laboratory of the Pontifical Catholic University of Goiás (PUC-GO), located in Goiânia, after due approval by the institution’s Ethics Committee. The main objective of the research is to investigate the effects of lavender essential oil solution (Lavandula angustifolia) on chorioallantoic membranes of embryonated eggs, focusing on identifying angiogenic (stimulating the growth of new blood vessels) or antiangiogenic (inhibiting this growth) activities. Carrying out this study allows a more in-depth understanding of the angiogenic and/or antiangiogenic properties of lavender essential oil, in addition to evaluating its safety for use in the treatment of various diseases within folk medicine. The results are expected to contribute significantly to the development of new products that can have a positive social impact, especially since lavender is an easily accessible, low-cost and renewable plant. Preliminary findings indicate that lavender essential oil has angiogenic activity and that the chorioallantoic membranes used in the tests showed excellent quality, exceeding expectations in quantifying vascularization in each phase of the project. These results reinforce the potential of lavender essential oil as an effective and safe therapeutic alternative.